Development of glutamic acid incorporated with fluorine ionic liquid for dissolution of solid scale - Adam, Fatmawati
Solid scale formation such as calcite (CaCO3), barite (BaSO4) and ferrite (FeS) in oil production is known to be one of the major problems that cost operator huge amount of expenditure. Chemical compound with carboxylic group and amine has been widely used due to its ability to dissolve and chelate metal ions in solid scale to prevent reprecipitation. This research aims to to synthesise and characterise the amino acid-based solid scale dissolver from monosodium glutamate (MSG). The second objective is to evaluate the dissolution of calcite and barite solid scale using synthesised amino acid-based solid scale dissolver. Acidification produces two amino based dissolver, glutamic acid hydrochloride (solid) and glutamic acid hydro fluoroborate (liquid). Metathesis produces glutamic acid trifluoromethyl sulfonate (liquid). Glutamic acid hydrochloride can dissolve 3865 ppm of calcium in 24 hours at 60 °C and less than 5ppm of barium. Glu-BF4 can dissolve up to 2381 ppm of calcium and only 74 ppm of barium. GluTFMS can dissolve up to 2013.5 ppm of calcium and 60.0 ppm of barite. Based on the dissolution result, GluCl, GluBF4 and Glu TFMS is a good dissolver for calcite as it can dissolve more than 2000 ppm of calcite at low concentration. Barite is known as the most difficult solid scale to dissolve. In this study, all dissolver synthesised can only dissolve less than 100 ppm of barite.